Analisis Pengasuhan Penuh Kesadaran (Mindful Parenting) dalam Menumbuhkan Kemandirian Anak di Aceh Selatan - Faridy, Faizatul; Khairina; Dewi Fitriani; Khairina, Khairina (Bunayya, 2026)
This study aims to analyze mindful parenting practices in fostering independence among children aged 5–6 years in South Aceh and to identify factors that hinder the implementation of these practices. A qualitative approach with a case study design was employed. The participants consisted of four mothers and four early childhood children selected through purposive sampling. Data were collected using structured observations, open-ended interviews, and documentation. Data analysis was conducted through triangulation to ensure the credibility of the findings. The results indicate that mindful parenting is practiced through attentive communication, parental emotional regulation, non-judgmental acceptance, and supportive involvement in children’s daily activities. These practices positively contribute to children’s independence, as reflected in their ability to perform self-care tasks, engage in social interactions, and demonstrate initiative in everyday activities. However, the implementation of mindful parenting is influenced by economic conditions, time constraints due to parental work demands, and the social environment. Despite these challenges, the findings highlight that the quality of parent–child interactions grounded in awareness and emotional presence remains a key factor in supporting children’s independence. This study provides valuable insights into the application of mindful parenting within a specific sociocultural context and contributes to the broader understanding of awareness-based parenting practices in early childhood education.